DAMPAK PERNIKAHAN BEDA AGAMA TERHADAP KETERLIBATAN HIDUP MENGGEREJA SEBAGAI UMAT BERIMAN KRISTIANI - Hendri Kusnadi; Albert I Ketut Deni Wijaya (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Marriage is a partnership between man and woman who have been baptized. It is monogamous and inseverable in nature. Dealing with the characteristic of catholic marriage, the church forbids the mixed marriage to occur. The prohibition is an attempt of the church to protect the Catholics’ faith from the risk of mixed marriage. In the other hands, the church creates a policy which is in the form of permission for mixed marriage. Further, this kind of marriage has impacts towards the church life. One of the impacts is causing intolerance in which the Catholics become inactive in the church life. Regarding the effect of interfaith marriage towards the involvement of church life as Christians, some problems are formulated such as : 1) what is the definition of interfaith marriage? 2) how is the church life of the people who commit interfaith marriage as Christians3) What are the effects of interfaith marriage towards their church life? In this research, Qualitative method is applied. Mean while, the method of interviewing (structural) is used to collect the data. The direct interviews are conducted privately between the parties. Moreover, the respondents of this research are the Catholics who undertake a mixed marriage at chapelry of Saint Vincentius A Paulo Jenangan. Based on the result of the research, there are three things which are found. First, people have lack of understanding about interfaith marriage. They are unable to differentiate between mixed marriage of different religion or church. Besides, they do not really understand the process of gaining permission to undertake the marriage. Second, people are not active in doing the activities in the church. They said that they only involved in 2 fields out of 5 church duties. Furthermore, there are negative effects of interfaith marriage, that is the intolerance of a party who is not catholic. In the case, the intolerance itself is the different opinion which causes anger and always be brought up. However, there are also some positive effects which appears from interfaith marriage. One of them is the tolerance of a non-Catholic party who always reminds his or her partner to go to the church.